The nature of 500 micron risers – II. Multiplicities and environments of sub-mm faint dusty star-forming galaxies. Issue 1 (28th November 2022) - Cairns, J; Clements, D L; Greenslade, J; Petitpas, G; Cheng, T; Ding, Y; Parmar, A; Pérez-Fournon, I; Riechers, D
ABSTRACT: We present Submillimeter Common User Bolometer Array 2 (SCUBA-2) and Submillimeter Array (SMA) follow-up observations of four candidate high-redshift dusty star-forming galaxies, selected as sources with rising spectral energy distributions in the 250, 350, and 500 μ m Herschel SPIRE bands. Previous SMA observations showed no counterparts to these sources, but in our deeper sub-mm observations we detect counterparts to all four 500 μ m risers, with three resolving into multiple systems. For these three multiple systems, the SMA 345 GHz (≈870 μ m) observations recover 123 ± 73 per cent, 60 ± 15 per cent, and 19 ± 4 per cent of the integrated 850 μ m flux density from SCUBA-2, indicating that there may be additional sources below our SMA detection limit making up a dense, protocluster core. The fourth 500 μ m riser was observed at a lower frequency and so we cannot make a similar comparison. We estimate photometric redshifts based on FIR/sub-mm colours, finding that three fourths likely lie at z ≥ 2. This fits with the interpretation that the 500 μ m riser selection criterion selects both intrinsically red, individual galaxies at z > 4, and multiple systems at more moderate redshifts, artificially reddened by the effects of blending. We use the SCUBA-2 850 μ m maps to investigate the environments of these 500 μ m risers. By constructing cumulative number counts and estimating photometric redshifts for surrounding SCUBA-2 detections, we find that one of our 500 μ m risers could plausibly reside in a z ≥ 2 protocluster. We infer that bright 500 μ m risers with faint 850 μ m flux densities are typically multiple systems at z ≥ 2 that may reside in overdensities of bright sub-mm galaxies.